Improving attitude towards green environment awareness through the slgea-code module - Rose Amnah, A.R. (2015)
This paper is part of a large study which was on developing a green environment awareness module using QRCode. My main focus of the study was on the development of the module. In this paper, I focus on the evalution phase of the module after it was taught by a teacher to two form four classes. The aim of the evaluation isto test whether students attitude can be nurtured to behave, act and react towards conservation of the green environment usingthe module. The researcher developed Green Environment Awareness Module with QR-Code (SLGEA-Code) as a self-learning and- mobile learning instructional approach. The module was evaluated on two classes one is the treatment group and the other is the control group. The evaluation phase employed a quasi-experimental design. Two groups of form four secondary students were the sample of the study. The researcher trained 1 experienced teacher to teach to 2 form Four classes; treatment class (n= 35) and compared gains in attitude towards green environment to the normal approach (control) class (n=33). The measure for attitudes towards the environment were adapted from the GASE scale. There were five domains; willingness to learn and inform about environmental issues; disbelief in explanations related to environmental issues; sensitivity towards environmental issues and saving the environment; disbelief in environmental, and belief in protecting habitat. Students in the treatment group showed statistically greater growth in their attitudes towards the environment in all the of the domains compared to the pre-test. This study revealed the potential of using a self-learning module to nurture students attitude towards caring for the environment by giving them massive and immediate information in a convenient, interesting and current way